A nomogram to identify appropriate candidates for breast-conserving surgery among young women with breast cancer: A large cohort study - Pu, Shengyu; Song, Shaoran; Chen, Heyan; Zhou, Can; Zhang, Huimin; Wang, Ke; He, Jianjun; Zhang, Jian (Frontiers in Oncology, 2022)
Background: There is a gradual increase of female breast cancer under 35 years old, who was characterized as poor prognosis. Whether young patients could obtain greater survival benefits from breast-conserving surgery (BCS) than mastectomy remains controversial. Methods: Breast cancer patients (≤35 years old) were selected from the Surveillance, Epidemiology, and End Results (SEER) database and divided into BCS and mastectomy group. Propensity score matching (PSM) was used to eliminate the distributional imbalance of variables among two groups. The influence of BCS on overall survival (OS) and breast cancer-specific survival (BCSS) was evaluated by Cox regression. Logistic regression was used to identify factors related to the benefit of BCS and to construct a nomogram. The nomogram was validated by the First Affiliated Hospital of Xi'an Jiaotong University cohort. Results: Totally, 15,317 cases in the SEER database and 149 cases of external validation cohort were included. BCS was an independent protective factor for OS (P = 0.028) and BCSS (P = 0.042). A nomogram was established, and the AUC values both in the internal and external validation set were 0.780. The applicability of the model was verified in the PSM cohort and indicated that the survival advantage in the BCS-Benefit group was higher than that in the BCS-Nonbenefit and mastectomy group (P <0.001). Conclusions: For young breast cancer patients, BCS may bring better OS and BCSS than mastectomy, but not all benefit from it. We constructed a model for young patients (≤35 years old) that could identify appropriate candidates who benefit from BCS.